Diabetes Mellitus and Hypertension among Patients on Combination Antiretroviral Therapy in Civil Service Hospital, Nigeria (Bangladesh Pharmaceutical Journal, 2020)
The utilization of combination antiretroviral therapy (cART) in the management of Human Immunodeficiency Virus (HIV) infection could lead to diabetes mellitus and hypertension. Therefore, this study was conducted to determine the incidence and risks for diabetes mellitus and hypertension amongst HIV-infected patients on cART at ART Clinic of Civil Service Hospital, Ilorin, Nigeria. Crosssectional research was conducted among 262 consented HIV-infected patients on cART from April to July 2018. Random blood sugar and blood pressure of the patients were measured with glucometer and sphygmomanometer, respectively. The subjects were administered with standardized sociodemographics, treatment, and clinical variable forms. Descriptive and inferential statistics were used, and ethical approval was obtained. The patients had a mean age of 44.32±11.60 years and had received cART for a median duration of 6.01± 2.16 years. There was a high incidence (18.3%) of hypertension and diabetes mellitus diseases among the patients on cART. The majority of 32 (66.67%) of the patients were on Efavirenz + Lamivudine + Tenofovir combination therapy. The risk factors for the comorbidity were gender (OR 1.113; 95% CI 0.014-0.938, p < 0.043), duration on HIV infection (OR 1.084; 95% CI 0.860-1.366, p < 0.049), duration on cART (OR 1.928; 95% CI 0.861-1.679, p < 0.048) and types of cART (OR 1.042; 95% CI 1.000-1.085, p < 0.047). The high incidence of the comorbid conditions in HIV-infected patients on cART affirms the necessity to integrate screening for these two concomitant diseases in the HIV program as part of a healthcare support strategy.Bangladesh Pharmaceutical Journal 23(2): 125-134, 2020